Transformation for sustainability and its promoting elements in educational institutions: a case study in an institution focused on transformative learning - Palma, Lisiane Celia; Pedrozo, Eugênio Ávila (Organizações & Sociedade, 2019)
This paper aims to identify what changes are necessary in educational institutions (EIs) to improve their potential as promoters of transformation for sustainability. Thus, a case study was conducted in an EI, in England, which seeks to promote transformative learning for sustainable living. Data were obtained through 8 interviews, analysis of 12 documents, and observations carried out in February and March 2014. Using the Sustainable Transforming Learning Framework and the elements that promoted the transformation to sustainability in EIs found in the literature as references, the case study was analyzed focusing on the processes of change for sustainability, management, and teaching-learning. Two of the main findings are: the adoption by the EI of sustainable strategies and objectives that go beyond the Triple Bottom Line, involving multiple stakeholders; the expansion of the teaching-learning process goes beyond cognitive objectives, adopting a strategy of sustainable education and transdisciplinarity.